BatchFLEX: feature-level equalization of X-batch - Davis, Joshua T; Obermayer, Alyssa N; Soupir, Alex C; Hesterberg, Rebecca S; Duong, Thac; Yang, Ching-Yao; Dao, Ken Phong; Manley, Brandon J; Grass, G Daniel; Avram, Dorina; Rodriguez, Paulo C; Fridley, Brooke L; et al. (Bioinformatics (Oxford, England), 2024)
Motivation Integrative analysis of heterogeneous expression data remains challenging due to variations in platform, RNA quality, sample processing, and other unknown technical effects. Selecting the approach for removing unwanted batch effects can be a time-consuming and tedious process, especially for more biologically focused investigators. Results Here, we present BatchFLEX, a Shiny app that can facilitate visualization and correction of batch effects using several established methods. BatchFLEX can visualize the variance contribution of a factor before and after correction. As an example, we have analyzed ImmGen microarray data and enhanced its expression signals that distinguishes each immune cell type. Moreover, our analysis revealed the impact of the batch correction in altering the gene expression rank and single-sample GSEA pathway scores in immune cell types, highlighting the importance of real-time assessment of the batch correction for optimal downstream analysis. Availability and implementation Our tool is available through Github https://github.com/shawlab-moffitt/BATCH-FLEX-ShinyApp with an online example on Shiny.io https://shawlab-moffitt.shinyapps.io/batch_flex/.